Pengembangan Karater Percaya Diri Siswa Kelas IV Melalui Metode Diskusi di SDN Bareng Krajan 2 Krian - Arto, Aldy Budi; Kurniawan, Machful Indra (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The research was conducted with the aim of describing the application of the discussion method in cultivating a confident character and to show an increase in the value of self-confidence in thematic learning in class IV B students at SDN Bareng Krajan 2 Krian. In this study the method used was classroom action research which was applied in 2 cycles. The subjects in this study were students of class IV B SD Bareng Krajan 2. The data collection technique in this study was obtained from the results of a questionnaire related to the value of the character of self-confidence in each cycle. The data analysis technique used in this study was carried out descriptively. The results obtained from the application of this discussion method can increase the value of the character of self-confidence which is shown from the average value obtained. The average self-confidence score of students in class IV B was 56.90 then in cycle I it became 64.25 and in cycle II it became 76.30 with an average score above the KKM which was 75.0 which had been determined by the researcher. The value of the character of self-confidence in class IV B students based on the acquisition of values ​​from the results of the questionnaire found an increase with the application of the discussion method to learning activities.